High throughput real‐time RT‐PCR assays for specific detection of cassava brown streak disease causal viruses, and their application to testing of planting material. (2nd May 2012) - Adams, I. P.; Abidrabo, P.; Miano, D. W.; Alicai, T.; Kinyua, Z. M.; Clarke, J.; Macarthur, R.; Weekes, R.; Laurenson, L.; Hany, U.; Peters, D.; Potts, M.; et al.
<x xml:space="preserve">Abstract</x> Cassava brown streak disease (CBSD) caused by Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV) is causing severe losses in cassava production in Kenya, Tanzania and Uganda. Two real‐time RT‐PCR assays based on TaqMan chemistry capable of detecting and distinguishing these two viruses are described. These assays were used to screen 493 cassava samples collected from western and coastal Kenya, the main cassava regions of Uganda and inland Tanzania. Both viruses were found in all three countries and across regions therein. Association of CBSD leaf symptom status with CBSV and UCBSV assay results was weak, confirming the need for a diagnostic assay. For leaf samples that were observed with CBSD‐like leaf symptoms but shown as CBSV and UCBSV negative by the RT‐PCR assay, deep sequencing using a Roche 454 GS‐FLX was used to provide additional evidence for the absence of the viruses. The probability of the CBSD associated diagnostics detecting a single CBSV or UCBSV positive sample amongst other non‐CBSD samples was modelled. The results of this study are discussed in the context of the application of diagnostics of CBSD‐associated viruses under the Great Lakes Cassava Initiative and the need to minimize the risk of further spread of the viruses with cassava multiplication material. It is shown that high throughput testing undertaken at Fera of 300 cassava leaves taken from fields for seed multiplication, when analysed in pools of 10, has given a 95% probability of detecting 1% infected plants in the field.